Satellite-based re-examination of changes in terrestrial near-surface wind speed in the last 30 years - Zhang, Wei; Zhang, Lishui; Liu, Jikai (Frontiers in Earth Science, 2024)
Wind plays a crucial role in shaping climate and environmental conditions; however, its spatial and temporal variabilities over land remain poorly understood. This study utilizes combined datasets from multiple satellite platforms to examine the spatial patterns and temporal trends of wind speed over land during the past 30 years . The results demonstrate a significant increasing trend in global wind speed, with variations on both annual and monthly scales. Spatially, wind speeds are lower in low-latitude regions, particularly in the tropics. High wind speeds primarily occur in mid-to high-latitude regions, with the highest speeds observed in the Arctic. Temporally, the wind speed trend is characterized by an increase in low-speed winds and a decrease in high-speed winds. Overall, wind speed shows a significant correlation with temperature in the Amazon, Northern Europe, and Central Asia. The negative wind-temperature correlation is confined to small regions in central North America and North Africa. The findings of this study help clarify wind trends, providing valuable insights for future research on global climate and environmental change.